PENGEMBANGAN PARIWISATA BUDAYA DI KOTA BANDUNG DALAM SUDUT PANDANG IMPLEMENTASI KERJA SAMA PEMERINTAH DENGAN BADAN USAHA - adi (Inovasi Pembangunan : Jurnal Kelitbangan, 2023)
Bandung is one of the tourist destinations in Indonesia which has a variety of tourism potentials. But currently, tourism that is developing in the city of Bandung is more towards creative and contemporary tourism, culture-based tourism itself does not appear and is well known from this city. This research was conducted with the initiation of these problems, with the aim of understanding the condition of cultural tourism in the city of Bandung. A qualitative approach is carried out using in-depth interviews. A literature search related to the Public-Private Partnership (PPP) scheme was also carried out with the aim of comparing the conditions that occur with the solutions that can be provided by the PPP scheme. The excavation results show that the condition of cultural tourism in the city of Bandung is less well-known than contemporary tourism. Bandung City Government has a big contribution to the conditions that occur. It is known that the government experienced various obstacles in the development of cultural tourism in the city. Based on pairing with the KPS concept, the patterns in KPS can be a solution in overcoming the obstacles faced by the Government in the development of cultural tourism in the city of Bandung.